Informed: The art of the science of preparing athletes - Gamble, P. (Informed in Sport Publishing, Coaching and Consulting, 2018)
With this new offering, we delve into the uncharted territory that lies between textbook theory and real-world application. Whilst research should guide practice, there is inevitably a need to interpret what findings mean in practice and apply this information with 'live' athletes.